Diagnostic challenges in non-cirrhotic portal hypertension - porto sinusoidal vascular disease - Nicoară-Farcău, Oana (World J Gastroenterol, 2020)
Non-cirrhotic portal hypertension consists of a group of diseases characterized by signs and complications of portal hypertension, which differ from cirrhosis through histological alterations, hemodynamic characterization and, clinical outcome. Because of the similarities in clinical presentation and imaging signs, frequently these patients, and particularly those with porto-sinusoidal vascular disease (PSVD), are misdiagnosed as having liver cirrhosis and thus raising difficulties in their diagnosis. The most challenging differentiation to be considered is between PSVD and cirrhosis and, although not pathognomonic, liver biopsy is still the standard of diagnosis. Although they still require extended validation before being broadly used, new non-invasive methods for the diagnosis of porto-sinusoidal vascular disease, like transient elastography, contrast-enhanced ultrasound or metabolomic profiling, have shown promising results. Another issue is the differentiation between PSVD and chronic extrahepatic portal vein obstruction, especially now when it is known that 40% of patients suffering from PSVD develop portal vein thrombosis. In this particular case, once the portal vein thrombosis occurred, the diagnosis of PSVD is impossible according to the current guidelines. Moreover, so far, the differentiation between PSVD and sinusoidal obstruction syndrome has not been clear so far in particular circumstances. In this review we highlighted the diagnostic challenges regarding the PSVD, as well as the current techniques used in the evaluation of these patients.